Investigate everything : federal efforts to compel Black loyalty during World War I - Kornweibel, Theodore (Indiana University Press, 2002)
Free speech for African Americans, during World War I, had to be exercised with great caution. The federal government, spurred on by a super-patriotic and often alarmed white public, determined to suppress any dissent against the war and enforce on the black population one hundred percent patriotism. These pressures were applied by America's modern political intelligence system, which emerged during the war. Its major partners included the Bureau of Investigation (renamed the FBI in 1935); the Military Intelligence Division; and the investigative arms of the Post Office and State departments. Numerous African American individuals and institutions, as well as 'enemy aliens' believed to be undermining black loyalty, became their targets. Fears that the black population was being subverted by Germans multiplied as the United States entered the war in April 1917. In fact, only a handful of alleged enemy subversives was ever identified, and none was found to have done anything more than tell blacks that they had no good reason to fight, or that German would win. Nonetheless, they were punished under wartime legislation which criminalised anti-war advocacy; in one notorious case, when federal officials were unable to prosecute an alleged spy, they concocted other charges with which to harass him for years, even after the war ended. A much greater proportion of blacks was disenchanted with the war than has been previously acknowledged. Considerable numbers were privately apathetic, while others publicly expressed dissatisfaction or opposition to the war. So serious was this disillusionment that the Military Intelligence Division initiated efforts to improve blacks' morale, but to little effect. In fact, black men evaded the draft at a much higher rate than did whites, and they were dealt with punitively when apprehended by the Bureau of Investigation. Black editors who openly criticised the government or forcefully condemned lynching faced the threat of suppression, and were forced to trim their editorial sails. Among those menaced were the editors of the "Chicago Defender", the most widely-read black newspaper, and the "Crisis", the NAACP's influential monthly magazine. Another black editor served a penitentiary sentence for protesting against the army's racist policies. And the leadership of the Church of God in Christ was repeatedly investigated and indicted for that denomination's belief that active participation in war was sinful. Although the federal intelligence establishment was not able to suppress all black disaffection during World War I, it forced black editors to censor themselves, compelled an entire church denomination to repeatedly defend its conscientious objection to war, threatened other individuals into prudent silence, and jailed hundreds of black men, without judicial proceedings, for failing to comply with the selective service system. All these efforts to silence black protest established precedents for further repression of black militancy during the post-war Red Scare, the subject of the author's book, "Seeing Red: Federal Efforts to Suppress Black Militancy, 1919-1925."